Comparação de sistemas de cultivo do feijão da seca em sucessão ao milho precoce - de Andrade Araújo , Geraldo A; Vieira , Clibas; Chagas, José Mauro (Revista Ceres, 2025)
In this study the following treatments were compared in Leopoldina and Ponte Nova, MG, Brazil: 1) maize plants removed from the plot, which had been prepared with plow and harrow before bean planting; 2) maize plants removed from the plot, which had been treated with herbicide before bean planting, without soil preparation; 3) beans planted in between maize rows after weed control by hoe; 4) beans planted in between maize rows after weed control by herbicide; 5) maize harvested before weed control by hoe, followed by bean planting and cutting of maize plants in pieces 30 to 40 cm long, which were scattered on the plot; 6) equal to treatment 5, except for the use of herbicide instead of hoe. For bean yield the best treatment was 6, and the worst were treatments 1 and 2.